Avaliação multidimensional da pessoa idosa com base na classificação internacional de funcionalidade, incapacidade e saúde: construção de instrumento - Medeiros, Emilene Nóbrega (2021)
Introduction: The assessment of the elderly’s health has as its starting point the global functionality, which must be carried out in a thorough way because, when ignored, there is a compromise of the functional systems causing cognitive impairment, postural instability, immobility, incontinence and communicative disability. Objective: To build a multidimensional assessment instrument for the elderly to be used in the Family Health Strategy as the basis for the International Classification of Functionality, Disability and Health, with the main goal of defining the multidimensional diagnosis and the team's care plan. Method: This is a methodological research, developed in three phases: 1) Identification of the most relevant IFC categories for multiprofessional care in the functional assessment of the elderly person; 2) Construction of the instrument for the multidimensional assessment of the elderly person; and 3) Validation of the Instrument's content and appearance. The study population / sample consisted of health professionals who worked on the Family Health Strategy and agreed to participate in the study. The study met the ethical aspects in research involving human beings, recommended by Resolution No. 466/12 National Health Council and was developed after approval by the Research Ethics Committee of the Health Sciences Center, at the Federal University of Paraíba. Results: The identification of the IFC categories allowed the construction of the first version of the Instrument for Multidimensional Assessment of the Elderly Person - IMAEP, structured in two parts: 1) Personal Factors, and 2) Categories Body Functions, Body Structures, Activities and Participation and Environmental Factors. After this construction, the IMAEP was submitted to Content and Appearance Validation by specialists, who suggested small considerations in the content and greater changes in its appearance, which should start with the Environmental Factors component, followed by Activities and Participation and later Structures of the Body and finally Functions of the Body. It was also suggested to include a space to define, based on the multidimensional assessment of the elderly, the multidimensional diagnosis in each of the instrument's components, to facilitate the development of the team's care plan at the end of the instrument. Conclusion: It was structured an instrument based on the theoretical model of the ICF, which can be used in the Family Health Strategy, with the main goal of defining the multidimensional diagnosis and the team's care plan for the elderly. The need to continue the study for the development of the clinical validation stage is recognized.